Advanced genes expression pattern greatly contributes to divergence in Verticillium wilt resistance between Gossypium barbadense and Gossupium hirsutum - He, Lu; Han, Zegang; Zang, Yihao; Dai, Fan; Chen, Jinwen; Jin, Shangkun; Huang, Chujun; Cheng, Yu; Zhang, Juncheng; Xu, Biyu; Qi, Guoan; Cao, Yiwen; et al. (Frontiers in Plant Science, 2022)
Verticillium, representing one of the world’s major pathogens, causes Verticillium wilt in important woody species, ornamentals, agricultural, etc., consequently resulting in a serious decline in production and quality, especially in cotton. G. hirutum and G. barbadense are two kinds of widely cultivated cotton species that suffer from Verticillium wilt, while G.barbadense has much higher resistance toward it than G. hirsutum. However, the molecular mechanism regarding their divergence in Verticillium wilt resistance remains largely unknown. In the current study, G. barbadense cv. Hai7124 and G. hirsutum acc. TM-1 were compared at 0, 12, 24, 48, 72, 96, 120, and 144 hours post-inoculation (hpi) utilizing high throughput RNA-Sequencing. As a result, a total of 3549 and 4725 differentially expressed genes (DEGs) were identified, respectively. In particular, the resistant type Hai7124 displayed an earlier and faster detection and signaling response to the Verticillium dahliae infection and demonstrated higher expression levels of defense-related genes over TM-1 with respect to transcription factors, plant hormone signal transduction, plant-pathogen interaction, and nucleotide-binding leucine-rich repeat (NLR) genes. This study provides new insights into the molecular mechanisms of divergence in Verticillium wilt resistance between G. barbadense and G. hirsutum and important candidate genes for breeding V. dahliadahliae resistant cotton cultivars.